2016
DOI: 10.1177/1602400315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early Outcome of Weil Osteotomy and Distal Metatarsal Mini-Invasive Osteotomy for Lesser Toe Metatarsalgia

Abstract: DMMO is a safe and reliable alternative to Weil osteotomy for metatarsalgia and can preserve ROM of the MTP joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 15 publications
3
16
0
4
Order By: Relevance
“…The complications of the Weil osteotomy, on the other hand, are relatively high, and a literature review recently undertaken includes the presence of floating toes, recurrence, transfer metatarsalgia and a few delayed unions and no unions [30]. Although there are few comparative studies between the two types of surgery, a recent publication indicates the greater range of motion (ROM) in the metatarsophalangeal joint after the osteotomy by MIS than after the Weil osteotomy [31], whereas Jarde et al [32] reported a series of Weil’s osteotomies where they found reduced mobility of the MP joint in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The complications of the Weil osteotomy, on the other hand, are relatively high, and a literature review recently undertaken includes the presence of floating toes, recurrence, transfer metatarsalgia and a few delayed unions and no unions [30]. Although there are few comparative studies between the two types of surgery, a recent publication indicates the greater range of motion (ROM) in the metatarsophalangeal joint after the osteotomy by MIS than after the Weil osteotomy [31], whereas Jarde et al [32] reported a series of Weil’s osteotomies where they found reduced mobility of the MP joint in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of surgery is to relieve pain and restore an ideal forefoot morphology with a normal distribution of pressure in the forefoot [16–18]. Multiple surgical procedures have been described for this syndrome [1, 1926]. However, the Weil osteotomy (and its modifications) has been the preferred technique employed by surgeons for many years in Europe [17, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple surgical procedures have been described for this syndrome [1, 1926]. However, the Weil osteotomy (and its modifications) has been the preferred technique employed by surgeons for many years in Europe [17, 26, 27]. This procedure consists of an open intra-articular osteotomy performed after preoperative planning based on the Maestro's criteria to calculate the appropriate metatarsal length from anteroposterior standing radiographs [9, 11, 27, 28], which provides longitudinal decompression.…”
Section: Introductionmentioning
confidence: 99%
“…Неефективність консервативного лікування визначає показання до хірургічного лікування, спрямованого на зменшення больового синдрому та нормалізацію структури переднього відділу стопи з метою нормалізації навантаження [8,9]. Для корекції М описано цілий ряд хірургічних технік, які передбачають укорочення відповідної плеснової кістки і представлені дистальними та проксимальними остеотоміями, резекційною артропластикою ПлФС [10][11][12]. Однак найбільшої поширеності набула остеотомія, запропонована L.S.…”
Section: вступunclassified
“…Цікаво, що суб'єктивна оцінка емоційного стану за шкалою оцінки якості життя SF-36 у хворих після Weilостеотомії виявилась вищою, ніж після інших дистальних остеотомій [12].…”
Section: обговоренняunclassified